2015
DOI: 10.1002/tkm2.1022
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic lateral abdominal wall hematoma treated with Kampo medicines

Abstract: Case:A 62-year-old woman presented with whiplash, bruised chest, and lateral abdominal wall hematoma with an arterial rupture. Keishibukuryogan (KBG), a traditional Japanese Kampo medicine, was administered for treatment of oketsu syndrome. Five days after the injury, cervical and chest pain were still present, and the subcutaneous hematoma had increased tremendously in size. KBG was discontinued and jidabokuippo (JDI) was administered. The subcutaneous hematoma improved dramatically. Outcome: Symptoms improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The individual herbal components of JDI have been confirmed to have antioxidant properties [5]. Moreover, we have previously demonstrated the antioxidant activity of JDI and have reported that JDI could be useful for not only contusions and sprains, but also for rib and extremity fractures [6][7][8][9]. In acute inflammation, reactive oxygen species are involved in enhancing vascular permeability resulting in swelling.…”
Section: Discussionmentioning
confidence: 99%
“…The individual herbal components of JDI have been confirmed to have antioxidant properties [5]. Moreover, we have previously demonstrated the antioxidant activity of JDI and have reported that JDI could be useful for not only contusions and sprains, but also for rib and extremity fractures [6][7][8][9]. In acute inflammation, reactive oxygen species are involved in enhancing vascular permeability resulting in swelling.…”
Section: Discussionmentioning
confidence: 99%
“…We have used JDI for various trauma such as rib fractures, fractures of extremities, abdominal wall hematoma, and traumatic asphyxia ( Nakae et al, 2012 ; Nakae et al, 2015a ; Nakae et al, 2016 ; Kitamura et al, 2022 ; Nakae et al, 2015b ; Nakae et al, 2020 .).…”
Section: Effectiveness Of Jidabokuippomentioning
confidence: 99%
“… a Calculated according to the previous reports ( Sudo and Oribe, 2005 ; Sakurai et al, 2006 ; Takeda, 2010 ; Nakae et al, 2012 ; Nakae et al, 2015a ; Yoshida, 2015 ; Hasegawa et al, 2016 ; Nakae et al, 2016 ; Saito et al, 2019 ; Kitamura et al, 2022 ). …”
Section: Safety Of Jidabokuippomentioning
confidence: 99%
“…The concept of blood stasis also involved hematoma and deep vein thrombosis. In university hospital, KBG was used for treating hematoma in emergency department (60). Kumanomido et al reported that KBG diminished subcutaneous hematoma after surgery in a case report (61).…”
Section: Varicose Vein Hematoma and Deep Vein Thrombosismentioning
confidence: 99%